Assessment of Renal Functions and Lesions in Dogs with Serological Diagnosis of Canine Visceral Leishmaniasis - Nadal, Niara Vanat; Campos, Sabrina Destri Emmerick; Azevedo, Estella Francisco de; Mendes Júnior, Artur Augusto Velho; Figueiredo, Fabiano Borges; Macieira, Daniel de Barros; Verícimo, Maurício Afonso; Almosny, Nádia Regina Pereira (Acta Scientiae Veterinariae, 2020)
Background: Visceral leishmaniasis is a complex vector-borne disease caused by the protozoan Leishmania infantum. In urban centers of South America, where this zoonotic cycle occurs, dogs seem to be the main reservoirs and infection sources. Animals with canine visceral leishmaniasis (CVL) may have a wide clinical spectrum, and dogs are usually classified as asymptomatic, oligosymptomatic, and symptomatic. Several organs are affected in canine CVL, and renal involvement is often a determining factor in dog prognosis. Nevertheless, serum markers are slow to indicate loss of renal function. The aim of this study was to evaluate kidney impairment in dogs diagnosed with CVL. Material, Methods & Results: Blood and urine samples were collected from 45 dogs from Barra Mansa-RJ, and used for urinalysis, urine protein/creatinine (UPC) ratio, and serum concentrations of urea and creatinine. The animals were classified as symptomatic (42.2%), oligosymptomatic (37.8%), and asymptomatic (20.0%). Some alterations were found in the urine samples; pale-yellow color in 17.8%, low specific gravity in 6.7%, turbidity in 51.1%, proteinuria in 80%, occult blood in 46.7%, bilirubin in 8.89%, and glucose in 6.7% of the samples. According to the UPC ratio, 60% of dogs were proteinuric, and UPC > 2.0 was high in symptomatic dogs. Azotemia was observed only in three dogs with CVL. Discussion: The majority of dogs presented one or more symptoms of CVL, as expected in an endemic area from Brazil. Pale-yellow urine was observed in some samples, and this change, when accompanied by the decreased urine specific gravity in dogs with CVL, suggests some degree of kidney disease. The presence of epithelial and red blood cells, leukocytes, bacteria, suspended mucus, and phosphate crystals that precipitate in alkaline urines could be associated, to some degree, with the urine turbidity found in the present study. The alkaline urine identified in some dogs could be related to the animals’ diet, but renal tubular acidosis (RTA) is another possible cause when referring to animals with CVL. The abnormal presence of bilirubin and glycosuria can be justified by liver damage and glomerular and tubular damage, respectively. Occult blood was found in the urine of almost half of the tested dogs, which occurred because of the presence of red blood cells in the urine sediment and hematuria in some animals, could be caused by tubular and glomerular lesions. The presence of granular and hyaline casts found in the samples reinforce the possibility of tubular injury. We found different levels of proteinuria; it was an important result, possibly caused by immune complex deposition in addition to tubular disease. Most tested dogs, including animals without clinical manifestation, were classified as proteinuric or borderline proteinuric, showing that the renal disease could be the only clinical manifestation of CVL and that it could progress from slight proteinuria to end-stage renal disease, resulting in chronic renal failure, which is the main cause of death. The UPC ratio > 2.0 was significantly the more frequent finding in this study, mainly in symptomatic dogs. This result indicates a glomerular disease in these animals, reinforcing that the progression of renal disease follows the clinical progression of CVL. A few serum samples showed increased urea and creatinine levels, proving that azotemia is an uncommon finding in CVL-infected dogs. In conclusion, urinalysis helped in the early identification of renal injury in CVL-infected dogs, highlighting elements that reinforce the presence of tubular or glomerular lesions, or both, even in non-azotemic dogs. The high frequency of symptomatic dogs with UPC ratio > 2.0 suggests a relationship between the progression of renal disease and the clinical progression of CVL.